2013
DOI: 10.1088/1748-0221/8/01/c01044
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an ultra-high-resolution parallel-hole collimator for CdTe semiconductor SPECT system

Abstract: Recently, there has been an increase in the demand for semiconductor detectors in the field of nuclear medicine imaging. The development of semiconductor detectors using materials such as CdTe that allowed for improved spatial resolution greatly advanced the field. However, the pinhole collimator that allows for high spatial resolution compromises the sensitivity due to the small size of the hole. An improvement in both sensitivity and spatial resolution may be achieved by using a pixelated parallel-hole colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…To improve both the system's sensitivity and spatial resolution, we recommend applying a pixelated parallel-hole collimator using a pixelated semiconductor detector. Based on previous study, this system achieved an approximately 0.70 mm spatial resolution with a source-to-collimator distance of 2 cm [15]. The increased sensitivity was attributed to the collection of gamma rays by each individual pixel.…”
Section: Resultsmentioning
confidence: 94%
“…To improve both the system's sensitivity and spatial resolution, we recommend applying a pixelated parallel-hole collimator using a pixelated semiconductor detector. Based on previous study, this system achieved an approximately 0.70 mm spatial resolution with a source-to-collimator distance of 2 cm [15]. The increased sensitivity was attributed to the collection of gamma rays by each individual pixel.…”
Section: Resultsmentioning
confidence: 94%
“…In a similar manner with photon-stopping power in terms of photon attenuation, increasing the linear attenuation coefficient was demonstrated to have potential effects on the improvement of the spatial resolution and, hence, on isotopic image quality, for example, image contrast, resolution, and detectability. 11 17 It should be noted that linear attenuation coefficient is also influenced by the beam energy. 21 22 Regarding image contrast, the value obtained for the 19.1 mm cold sphere inside the Deluxe phantom increased by 1.32, 1.16, and 1.01 with W_ha193, W_he397, and W_he3925 compared to the Pb, respectively ( Table 6 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 Lee et al have shown from Monte Carlo simulations that the use of U provided about 3.19, 4.19, and 8.01% higher spatial resolution compared to Au, W, and Pb, although the system sensitivity of Pb was determined 4.25, 6.53, and 10.28% compared to the W, Au, and U, respectively. 17 In 2013, Weng et al, showed that imaging systems with a W parallel-hole collimator and cadmium zinc telluride (CZT) detectors compared to using Pb with a conventional NaI(Tl) detector have reduced the amount of septal penetration, image noise, and sharpness, and they concluded that the reduction may be attributed to W linear attenuation coefficient and also better energy resolution of CZT detector. 18 In another study by Lee et al, it was shown that the spatial resolution of U, with the same sensitivity, was better than Pb, W, and Au.…”
Section: Introductionmentioning
confidence: 99%
“…Its useful properties consist of a wide band gap (1.44 eV) with a high resistance (10 9 Ω),[ 2 ] high atomic number (Cd: 48 and Te: 52), and high density (5.85 g/cm 3 ) which provide a better absorption characteristics. [ 31 32 ] Because of the high absorption, CdTe can be applied for detection of energetic photons. Absorption of photons in the material can be computed by the following formula:…”
Section: Cadmium Telluride Detectormentioning
confidence: 99%
“…The imaging of dual-radioisotopes will provide two functional images without time difference and position error by a single scan. [ 30 31 32 33 34 35 36 37 38 39 40 41 42 ] The planar images of a brain phantom from both CdTe and NaI(Tl) detectors are demonstrated in in Figure 5 . [ 20 ] The images from CdTe detector have higher contrast and sharpness due to well scatter rejection.…”
Section: Medical Imaging With Cadmium Telluride Detectormentioning
confidence: 99%